Sisters of Tomorrow : The First Women of Science Fiction - Goonan, Kathleen Ann; Sharp, Patrick B., 1967-; Yaszek, Lisa, 1969- (Book collections on Project MUSE., 2016)
Anthology of stories, essays, poems, and illustrations by the women of early science fiction.